Designing an International Large-Scale Assessment of Professional Competencies and Employability Skills: Emerging Avenues and Challenges of OECD's PISA-VET - Andreas Rausch; Stephan Abele; Viola Deutscher; Samuel Greiff; Viktoria Kis; Sally Messenger; Jenny Shackleton; Lucia Tramonte; Michael Ward; Esther Winther (Vocations and Learning, 2024)
Globally, vocational education and training (VET) is considered important for ensuring the supply of skilled labour to the economy and economic competitiveness but also for helping the next generation with the transition to working life and integration into society. However, despite this importance, there are no international comparative studies on the effectiveness of the very different VET systems. In March 2024, the Organisation for Economic Co-operation and Development (OECD) published the `Analytical and Assessment Framework' for PISA-VET, an international study on professional competencies and employability skills in VET. In this paper, some of the lead experts that contributed to the framework provide an outline of the aims of the initiative, the target groups, the assessment approaches as well as strength and weaknesses to stimulate discussion in the scientific community. VISA-VET aims to deliver comprehensive data, inform decision making, facilitate peer learning between countries, and promote the image of VET, in general. Target populations are learners toward the end of their VET programmes in the occupational areas of automotive technicians, electricians, business and administration, health care, or tourism and hospitality. Assessment approaches to domain-specific professional skills are simulation-based questions, digital simulations, and live or recorded demonstrations. The professional skills assessments are expanded by the assessment of employability skills and comprehensive data collections on national contextual and system-level factors. This paper discusses the selection and breakdown of occupational areas, the various assessment approaches and possible supplementary studies. Its overall aim is to initiate a broader discussion in the scientific community about the design of and expected insights from PISA-VET.
Keywords: 370; PISA-VET; Vocational education and training; Large-scale assessment; Educational assessment; Professional competences; Employability skills